High-Throughput Screening of Novel Indole Alkaloids as Potential Tyrosine Kinase Inhibitors for Breast Cancer Therapy - Mhaske, Ganesh S.; Ganage, Asmita D.; Satkar, Shraddha S.; Awate, Shyam S.; Gurav, Mayuri V.; Sribhavani, K.R; Phadtare, Ganesh; Waghmare, Shubham (Current Biotechnology, 2025)
IntroductionBiotechnology provides the biological data and molecular insights that drive Computer-Aided Drug Designing (CADD), which is an advanced computational technique used in drug discovery and development. It integrates biological, chemical, and computational tools to identify and optimize potential therapeutic compounds. Its connection with biotechnology is significant. The importance of the indole moiety in drug discovery emphasizes its privileged status in finding new drug molecules. Understanding the functions of indole alkaloids, as well as structure-activity relationships (SARs) of indole derivatives and receptor tyrosine kinases, such as the platelet-derived growth factor receptor (PDGFR), is critical for developing targeted therapies for various diseases like breast cancer. Rational drug design is found to be important in the drug development process. The aim of the current investigation is to find, explore, and optimize indole alkaloids against receptor tyrosine kinases as a promising avenue in drug discovery and development, particularly in the context of breast cancer treatment employing a computational approach.MethodsChemAxon Marvin Sketch 5.11.5 was used to create 2D structures of indole alkaloids. The physicochemical characteristics of indole alkaloids, as well as their toxicity, were predicted using Swiss ADME & pkCSM online web tools. Molecular docking technology was used to examine the ligand-receptor interactions of indole alkaloids with the target receptor (PDB: 5GRN) using various programs, including Autodock 1.1.2, MGL Tools 1.5.6, Discovery Studio Visualizer v20.1.0.19295, Procheck, Protparam tool, and PyMOL.ResultsAll indole alkaloids and their derivatives were determined to be orally bioavailable, less toxic, and have acceptable pharmacokinetic properties according to in silico studies. In comparison to the traditional medication Sunitinib, all indole alkaloids displayed higher docking scores.DiscussionThe indole alkaloids increase their potential as a novel therapy alternative for breast cancer and could facilitate more comprehensive in vivo, in vitro, chemical-based and pharma studies by medicinal chemists. As of now, our work is limited to in silico investigation of indole analogues, which will lay down a strong foundation for medicinal chemists to explore indole alkaloids.ConclusionThe increase in binding energy and the quantity of H-bonds created by indole alkaloids with interactions at distances below 3.40A provide a helpful starting point for isolating indole alkaloids that are most suitable for additional research. The application of indole alkaloids as a potential new cancer treatment candidate is supported by their pharmacokinetics and toxicological profile, which may aid medical chemists in conducting more in-depth in vitro and in vivo chemical and pharmacological studies.
Keywords: pharmacokinetics